The Function of Proverbs as Educational Media: Anthropological Linguistics on Wolio Proverbs - Firman Alamsyah Mansyur; Laode Achmad Suherman (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study aims to explain the function of proverbs as an educational media in the socio-cultural life of Wolio people in Southeast Sulawesi. The method used in this study was a descriptive qualitative in anthropological linguistics perspective. Data collected through observation and in-depth interviews. Data analysis departs from language analysis and then cultural analysis. This study concludes that Wolio proverb as an educational medium has five important functions in the social life of Wolio people, namely as a means to: (1) teach linguistic knowledge, (2) train the performance of Wolio young people in speaking, (3) instill values wisdom for young people, (4) controlling young people's behavior to conform to agreed norms, and (5) educating Wolio youths to own and uphold their life principles. From these findings, this study confirms that proverbs are a good educational medium because they contain linguistic knowledge and positive cultural values so that they must be kept and preserved by their supporting communities. The role of the government is very important to support the preservation of this proverb.